2022
DOI: 10.3390/su141710623
|View full text |Cite
|
Sign up to set email alerts
|

Media Information, Flood Images, and Perceptions in Times of Flood

Abstract: Disasters in Malaysia are managed using a framework developed through Directive 20 by the National Security Council. This framework is widely used in managing floods on the East Coast of Peninsular Malaysia. However, the prolonged rains that occurred on 17 December 2021 tested the capabilities of the existing framework: the rains caused floods in urban areas, which is unusual. This study was conducted to investigate the flood situation using data from the media, observations of the affected area, and people’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The situation clearly shows a gap in coordination, command, control, and communication in disaster management, resulting in a delayed decision-making process and causing casualties and considerable damage. The floods revealed that Malaysia's capacity to deal with large-scale disasters is inadequate, as state and federal agencies struggled with ineffective handling and coordination (Zahari et al, 2022). The tragedy raised several disturbing questions, including whether standard disaster protocols had been adhered to (Kamaludin, 2021;Lee, 2021).…”
Section: Malaysia's 2021 Flood: Case Study Of Military's Involvement ...mentioning
confidence: 99%
“…The situation clearly shows a gap in coordination, command, control, and communication in disaster management, resulting in a delayed decision-making process and causing casualties and considerable damage. The floods revealed that Malaysia's capacity to deal with large-scale disasters is inadequate, as state and federal agencies struggled with ineffective handling and coordination (Zahari et al, 2022). The tragedy raised several disturbing questions, including whether standard disaster protocols had been adhered to (Kamaludin, 2021;Lee, 2021).…”
Section: Malaysia's 2021 Flood: Case Study Of Military's Involvement ...mentioning
confidence: 99%
“…This country is prone to unpredicted floods, which leaves the populace unprepared. Landslides, mud floods, urban floods, and monsoon floods are common in Malaysia (Zahari et al, 2022). The magnitude, location, and timing of monsoon floods change annually.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reconstructing homes or other forms of shelter for those who lost them in the disaster is an important part of the recovery process. In any case, it is essential to do research on the level of satisfaction that residents have with the healing process because this affects their well-being either directly or indirectly (Yulianto et al, 2021;Zahari et al, 2022). According to the findings of a previous study conducted in the Philippines, residents' levels of happiness with the new homes they had purchased following a natural disaster were generally related to the degree to which the homes were suitable for the region, including in terms of thermal comfort and construction quality (Carrasco et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%